2005
DOI: 10.1063/1.1916186
|View full text |Cite
|
Sign up to set email alerts
|

Studying vocal fold vibrations in Parkinson’s disease with a nonlinear model

Abstract: A nonlinear model is applied to study pathologic vocal vibratory characteristics and voice treatments of Parkinson's disease. We find that a number of pathologic vocal characteristics commonly observed in Parkinson's disease, including reduced vibratory intensity, incomplete vocal closure, increased phonation threshold pressure, glottal tremor, subharmonics, and chaotic vocal fold vibrations, can be studied with this nonlinear model. We also find that two kinds of clinical voice treatments for Parkinson's dise… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
0
3

Year Published

2008
2008
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(37 citation statements)
references
References 54 publications
1
33
0
3
Order By: Relevance
“…There are a number of similarities between our results and the results of studies on abnormal phonation in pathological voice conditions involving edema, vocal folds polyps, nodules, and cysts, among others ͑Herzel et al., 1994, Berry et al, 1996, Titze, 1994a, Giovanni et al, 1999a, Giovanni et al, 1999b, Švec et al, 1999, Jiang et al, 2003, Zhang and Jiang, 2004, Zhang et al, 2005, Jiang et al, 2006. As in the Jiang et al ͑2003͒ excised experiments, we found that the acoustic signal showed signs of irregular phonation, and that non-linear methods worked better than classic perturbation methods for characterizing baseline versus viscosity conditions.…”
Section: Discussionsupporting
confidence: 61%
See 3 more Smart Citations
“…There are a number of similarities between our results and the results of studies on abnormal phonation in pathological voice conditions involving edema, vocal folds polyps, nodules, and cysts, among others ͑Herzel et al., 1994, Berry et al, 1996, Titze, 1994a, Giovanni et al, 1999a, Giovanni et al, 1999b, Švec et al, 1999, Jiang et al, 2003, Zhang and Jiang, 2004, Zhang et al, 2005, Jiang et al, 2006. As in the Jiang et al ͑2003͒ excised experiments, we found that the acoustic signal showed signs of irregular phonation, and that non-linear methods worked better than classic perturbation methods for characterizing baseline versus viscosity conditions.…”
Section: Discussionsupporting
confidence: 61%
“…A similar explanation may apply to the pathological voices examined by Herzel et al, 1994, Berry et al, 1996, Titze, 1994a, Giovanni et al, 1999a, Giovanni et al, 1999b, Švec et al, 1999, Jiang et al, 2003, Zhang and Jiang, 2004, Zhang et al, 2005, Jiang et al, 2006, and Zhang and Jiang, 2008 In addition, we found that the non-linear measures were particularly sensitive to differences in viscosity. For example, both correlation dimension and the Lyapunov exponent were able to identify difference between thin liquid and honey.…”
Section: Discussionmentioning
confidence: 66%
See 2 more Smart Citations
“…[3][4][5] Vibration of the vocal folds results from interactions between the vocal folds and multiple factors, including glottal airflow, vocal tract acoustics, and subglottal acoustics. The interaction between glottal airflow and vocal fold tissue is intrinsic to vocal fold vibration.…”
Section: Introductionmentioning
confidence: 99%